Central America [2012] - Amador Astúa, Jorge Alberto (2013)
For this region, nine stations from five countries were analyzed. The stations located on the Caribbean slope are: Phillip Goldson International Airport, Belize; Puerto Barrios, Guatemala; Puerto Lempira, Honduras; and Puerto Limón, Costa Rica. The fol- lowing stations are located on the Pacif ic slope: Tocumen International Airport and David, Panamá; Liberia, Costa Rica; Choluteca, Honduras; and San José, Guatemala. The analysis follows Amador et al. (2011) for all variables, except that the base period for computing anomalies was 1981–2010.